Philichthys xiphiae (Copepoda; Philichthyidae) - an interesting cranium parasite of the swordfish Xiphias gladius collected from the Baltic Sea. - Rolbiecki, L., B. Arciszewski & J.N. Izdebska (Oceanological And Hydrobiological Studies, 2021)
The swordfish, Xiphias gladius Linnaeus, 1758, is a fish that sporadically enters the Baltic Sea. The present paper describes the identification of a very rarely recorded and poorly studied copepod of the family Philichthyidae - Philichthys xiphiae Steenstrup, 1862 - in a dead swordfish found on a sea beach in Dzwirzyno (Poland) in 2016. Philichthyidae are parasites inhabiting the sensory canals in the lateral line and skull bones of marine fish. In the present case, two P. xiphiae females were found, which constitutes the first record of the species in the Baltic area.